The applicability of wildlife value orientations scales to a Muslim student sample in Malaysia - Zainal Abidin, Zulkhairi Azizi; Jacobs, Maarten H. (Taylor & Francis, 2016)
This article addresses the applicability of quantitative wildlife value orientation scales in Muslim students in Malaysia. As Malaysian culture is deeply influenced by Islam ideology, this article presents a case for addressing the cross-cultural applicability of the scales. The current wildlife value orientation scales were reliable—all Cronbach’s alphas ≥ .65—and had predictive validity—8 to 14% of variance of acceptability of lethal control was explained. Yet, both reliability and predictive validity were of lesser magnitude than figures in previous Western studies. Especially the hunting beliefs scale did not reflect basic thinking about wildlife in our sample, and our data suggest two different hunting dimensions—consequences of hunting for wildlife and human opportunities for hunting. For future cross-cultural comparisons of wildlife value orientations, amendment of the scales to better reflect salient beliefs in non-Western nations is recommended.